2019
DOI: 10.1038/s41526-019-0080-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal time course of muscle impairments during partial weight-bearing in rats

Abstract: In the near future, space agencies plan to send the first crews for extended stays on the Moon and Mars, where gravity is significantly reduced compared to Earth (0.16× g and 0.38× g , respectively). However, the long-term effects of partial gravity have not yet been elucidated, and ensuring astronauts’ health and performance is crucial to the success of these missions. Using a quadrupedal partial weight-bearing (PWB) model in rats that we designed, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 43 publications
3
28
2
Order By: Relevance
“…Similarly to our previous observations of PWB in male rats (Mortreux et al, 2018), we showed that the PWB system is extremely steady and reliable over time with a coefficient of variation (CoV) of 2.1% during the 2-week experiment. Despite being greater than the 1.2% CoV value in male animals previously reported by our group for periods of 2 to 4 weeks (Mortreux et al, 2019a), the CoV reported here remains well below our target range of ±5%.…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…Similarly to our previous observations of PWB in male rats (Mortreux et al, 2018), we showed that the PWB system is extremely steady and reliable over time with a coefficient of variation (CoV) of 2.1% during the 2-week experiment. Despite being greater than the 1.2% CoV value in male animals previously reported by our group for periods of 2 to 4 weeks (Mortreux et al, 2019a), the CoV reported here remains well below our target range of ±5%.…”
Section: Discussioncontrasting
confidence: 84%
“…Overall, females appear to tolerate well the period of partial mechanical unloading. While PWB led to a transient body weight loss in male rats (Mortreux et al, 2018(Mortreux et al, , 2019a,c), we did not observe any significant fluctuations of the females' body weight, either compared to the control group or to their pre-suspension baseline. This sex-based difference has been reported previously after exposure to 14 and 30 days of hindlimb unloading (Il'ina-Kakueva, 2002;David et al, 2006;Chang et al, 2018;Deschenes et al, 2018), and in our study, was further associated with a similar food intake, which was eventually greater at the end of the experiment in the PWB40 group when normalized to animals' body weight, compared to the PWB100 controls.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations